Thermal stability of B-based multilayer mirrors for next generation lithography - Naujok, P.; Murray, K.; Yulin, S.; Patzig, Christian; Kaiser, N.; Tuennermann, A. (Thin Solid Films, 2017)
The evolution of microstructure and reflective properties in a La/B4C and LaN/B4C multilayer was studied at elevated temperatures up to 800 °C. It was shown, that the observed opposite period thickness changes in La/B4C and LaN/B4C multilayers during annealing are based on structural modifications and chemical reactions at the interfaces. For T > 400 °C the period thickness of the La/B4C multilayer decreased, while it increased drastically in the LaN/B4C multilayer, which is explained by the formation of LaB6 crystallites and amorphous BN compounds, respectively. These thermally induced processes also lead to reflectivity drops at the wavelength of 6.7 nm for both investigated systems. Even after annealing at 800 °C for 10 h the LaN/B4C multilayer showed an EUV reflectance of 12.6%, with is significantly higher than the La/B4C multilayer (2.3%), pointing up their higher thermal resistance.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Boron nitride; EUV; Lanthanum hexaboride; Multilayer mirrors; Soft X-rays; Thermal stability